Antiproliferative Effect of 4-Methylumbelliferone in Epithelial Ovarian Cancer Cells Is Mediated by Disruption of Intracellular Homeostasis and Regulation of PI3K/AKT and MAPK Signaling - Garam An; Sunwoo Park; Minkyoung Lee; Whasun Lim; Gwonhwa Song (MDPI AG, 2020)
Ovarian cancer has a high mortality rate and high resistance to chemotherapy. Thus, many studies are currently assessing the ability of natural products to induce ovarian cancer cell death. A coumarin derivative, 4-methylumbelliferone (4-MU), has been reported to have anti-cancer effects on various cancers, but its effects on ovarian cancer are not fully understood. In this study, we identified the intracellular mechanism underlying the effects of 4-MU on epithelial ovarian cancer cells. Decreased ovarian cancer cell proliferation and an accumulation of cells in the G2/M phase were observed following 4-MU treatment. Moreover, 4-MU interfered with calcium homeostasis; induced endoplasmic reticulum stress in both cell lines; inhibited AKT and S6 phosphorylation; and increased ERK1/2, P38, and JNK phosphorylation. Furthermore, 4-MU and pharmacological inhibitors showed synergic effects in suppressing cell proliferation. Collectively, our current data indicate that antitumor effects of 4-MU could be appropriate for use as a therapeutic agent against epithelial ovarian cancer cells.